Efficiency of the Original Methods of Using Medicines and Early Enteral Nutrition in the Complex Treat Ment of Patients with Acute Pancreatitis - Andryushchenko V.; Andryushchenko D.; Kunovsky V.; Mahlovany V. (Львівський клінічний вісник)
Introduction. In addition to the implementation of adequate surgical tactics, the noninterventional component of treatment, aimed at correcting mechanisms for the appearance and increase of the severity of acute pancreatitis, becomes more and more important. The aim of the study. To work out new methods and to improve the existing ones of medical therapy in the complex treatment of patients with acute pancreatitis. Materials and methods. 329 patients with acute pancreatitis were examined. To perform each fragment of the study, two random groups of patients were formed, the experimental ones, for which the complex of the worked out noninterventional methods were implemented, and comparision ones with the traditional therapeutic approaches. There were used clinical, laboratory, biochemical, radiological (Xray, ultrasonographic, computed tomography), research methods were used to examine the patients. The obtained results were processed by the methods of variation statistics using Student’s criteria and χ². Results. Antisecretory treatment of a sample of 73 patients (women 38, men 35, aged 34 ± 2.4 to 47 ± 11.2 years), divided into two groups, was provided. The experimental one was formed of 46 patients, antisecretory treatment for which according to the «Method of treatment of acute pancreatitis using proton pump inhibitors», based on the use of pantoprazole (40.0 mg per day iv / 400.0 ml 0.9% solution of NaCl for 57 days), or with the following, according to the original «Method of step therapy with the use of proton pump inhibitors in the treatment of acute pancreatitis», transition to its oral administration (1 tablet of pantoprazole 40.0 mg once a day with the total treatment duration up to 14 days) was performed. The comparative group included 27 persons who used octreotide (injected at a dose of 100.0 μg 3 times a day for 5 days, and in cases of severe illness 1200.0 μg/day IV)) to suppress the secretory function of the pancreas. Analysis of the dynamics of amylase content in urine as an indicator of the effectiveness of hyperenzyme activity inhibition on the 1st, 3rd and 5th day showed that at the time of hospitalization the amylase level was almost identical in both groups of the examined subjects 880.4 ± 20.2 units and 910.4 ± 18.4 units (p > 0,05) with the reference value of 470.0 units. During the study of the effectiveness of the developed scheme of antisecretory treatment influence on the upper gastrointestinal tract (UGIT) in 62 patients, using the results of esophagogastrofibroscopy, the positive dynamics was noted in all the subjects. Since the edematous and exudative lesions of the pancreatic and retroperitoneal cellular tissue that occur in case of acute pancreatitis are a substrate of probable infection, the possibilities of its elimination in 64 patients (women – 28, men 36 at the age from 47.0 ± 4.3 to 56.0 ± 7.1 years), divided into two groups were also studied. The main group consisted of 38 people, whose complex of treatment was supplemented by diosmingesperidinecontaining substance of flavonoids normoven (4 tablets per day for a week), according to the “Treatment of acute edematous / interstitial pancreatitis”. The comparison group included 26 patients who received usual medical treatment. Analysis of the dynamics of edematous and exudative changes in the parapancreatic retroperitoneal cellular tissue in accordance with the results of ultrasonography showed that in the experimental group in contrast to the comparison group, on the third day of treatment, statistically significant decrease of the parapancreatic edema sizes with a reliable tendency to further normalization during the next days was observed. In addition, in the majority of patients from the experimental group (32; 84.0 %) the aseptic inflammation of both the pancreas and retroperitoneal cellular tissue was observed. Only 6 patients (16.0 %) had pancreatic necrosis and purulentnecrotic parapancreatitis/paraclitus (χ2 = 4.289; p = 0.038). In the comparison group, aseptic inflammatory process persisted only in 15 persons (58.0 %), and the infectious factor was confirmed in 11 persons (42.0 %) χ2 = 0.62923; p = 0.4. As the clinical course of the сhronic pancreatitis is accompanied by a rather intense and persistent pain syndrome, which, besides the negative influence on the condition of the patient, is a significant factor in the increase of the severity of the pathological process. The effectiveness of the analgesic effect was assessed by indirect measurement using the visual analog scale (VAS). As a biochemical criterion, the blood cortisol stress hormone content was used. This segment of the study included a sample of 62 patients (women 22, men 40 at the age of 37.0 ± 4.4, 54.0 ± 6.2 years) with the acute pancreatitis divided into two groups with different treatment schemes. The application of the proposed method allowed to achieve a positive analgesic effect according to VAS score during the 1st day in 32 patients of the experimental (84.0 %), and only in 14 patients (61.0 %); (p < 0.05) of the comparision group. The level of cortisol content in the blood in the experimental group decreased till the 3rd day from 1041.0 ± 12.0 nmol / L nmol / l to 685.0 ± 24.0 nmol / L nmol / l (p < 0.05), whereas in the comparison group, similar dynamics was not observed 997.0 ± 18.0 nmol / L nmol / l and 786.0 ± 21.0 nmol / L nmol / l (p > 0.05) respectively. The use of antibacterial agents, in particular antibiotics, is an important but controversial segment of the acute pancreatitis treatment program. In view of this, the principle of use of the antibacterial drugs in the mode of preventive antibiotic therapy in the presence of pancreatic necrosis has been worked out in order to prevent the probable attachment of the infectious factor to the primary aseptic inflammation of the pancreas. Early enteral nutrition (EEN) is also a significant factor in the treatment of acute pancreatitis. The methods of its conduct were improved and the effectiveness was evaluated in 82 patients (women 31, men 51, ages 43.0 ± 4.3, 55.0 ± 5.1 years) – 28 with moderate severity (34.0 %) and 54 (66.0 %) with the severe course of the acute pancreatitis. Analysis of the dynamics of clinical manifestations of motor and evacuation function of the intestine disorders has shown that in patients with enteral nutrition, dyspeptic disorders completely disappeared up to the 3rd day, abdominal bloating also disappeared and normal peristalsis appeared. Instead of this, the phenomena did not completely alleviate in the comparison group. A comparative analysis of the pathomorphological changes of the mucous membrane of the proximal part of the small intestine according to the results of the pathogistological studies has shown that after the EEN according to the proposed scheme, the number of patients with manifestations of microstructural changes in the wall significantly decreased. Suboperative evaluation of changes in the place of purulent necrotic inflammation of the pancreas and retroperitoneal cellular tissues during the provision of the stage surgical sanitations relaparotomy (RLT) showed that in case of EEN, an earlier «purification» of purulent necrotic areas from deviated tissues, inflammatory exudate and pus with the start of the reparative processes occured. Instead of this, in the comparative group, the same terms of such a positive dynamics were not observed. Conclusions. The implementation of original techniques, in particular antisecretory therapy, leveling of edema exudative lesions of parapancreatic retroperitoneal fluid, correction of metabolic disorders, multimodal analgesia, and improved method of early enteral nutrition, contributed to the improvement of treatment efficacy in comparison with traditional medication therapy, were proposed. The shown positive clinical outcome and the availability of the proposed techniques are advised to use in the work of medical institutions of practical health.